Facilities Management Business Opportunities - Khadijah Md Ariffin; Sani Inusa Milala; Rozilah Kasim (International Journal of Sustainable Construction Engineering and Technology, 2022)
Facilities management (FM) is a profession that has an enormous scope of business opportunities and it has become one of the fastest-growing sectors in the recent decade. FM’s scope and identity is a heterogeneous field that involves a wide range of tasks, responsibilities, and knowledge. This study primarily aimed at exploring the FM business opportunities and employed a systematic and intensive literature review. The study collected 93 journals from 3 search databases i.e Science Direct, Scopus and Emerald. The study found that there are numerous facilities management business opportunities, including construction, production, health and also maintenance. FM business shows high growth potential as the world continue to develop. This study proves numerous and evolving opportunity in FM business as new technology is used in the industry.